ANALISIS PENINGKATAN EKONOMI MASYARAKAT MELALUI USAHA EKONOMI KERAJIANAN ANYAMAN PANDAN DI DESA SUNGAI UKOI KABUPATEN SINTANG - Avelius Dominggus Sore; Yopinus Bobi (STKIP Persada Khatulistiwa Sintang, 2023)
The results showed that Community Empowerment through Pandan Weaving Handicraft Business in Desa Sungai Ukoi Kecamatan Sungai Tebelian Kabupaten Sintang, could improve the economic condition of the community to reduce unemployment by opening up job opportunities for the community and preserving handicraft activities, especially pandanus weaving, able to prosper the community and society. In improving the economy, which is getting better, namely through the awareness stage, which is done by providing counseling to the community, the capacity strengthening stage is carried out by providing training, namely, and the independence stage to see how far the implementation of the pandanus woven craft is.